Pengaruh Lama Penyimpanan dan Pengenceran Lindi Hitam Terhadap Karakteristik Lignin Kraft Acacia mangium - Faizatul Falah; Rikna Naila Salsabila; Wita Pradiani; Azizatul Karimah; Muhammad Adly Rahandi Lubis; Arief Heru Prianto; Nissa Nurfajrin Solihat; Fahriya Puspita Sari; Rita Rusman; Irawan Kusuma Wijaya; Widya Fatriasari (Jurnal Riset Kimia, 2022)
This study aimed to investigate the effects of storage time and dilution of black liquor (BL) from Acacia mangium kraft pulping on the characteristics of isolated Lignin. Lignin isolation was carried out by 1 and 2 steps of isolation using HCL 1M to precipitate Lignin, diluted before isolation. Isolated Lignin was analyzed for its acid-soluble Lignin (ASL), insoluble acid lignin (AIL), functional groups by FTIR, solubility in dioxane and NaOH and thermal properties. The effect of BL storage time was also evaluated on the characteristics of the Lignin produced. The results suggest that the longer BL is stored, the higher the lignin yield. When compared to the isolation approach without dilution, the dilution process produced a higher yield and ash content up to 84% and 21%, respectively. Without dilution, the AIL isolated was lower than the dilution during BL storage. The longer the storage duration, the higher the lignin purity. Compared to two-step lignin isolation, dilution treatment in single-step isolation improves yield and purity. The thermal stability of lignin isolation without dilution (184 ⁰C and 167 ⁰C for 1 and 2 steps, respectively) was higher than that of isolated Lignin with dilution (154.8 ⁰C and 160.9 ⁰C for 1 and 2 steps, respectively), according to thermal study. Both lignin isolates with and without dilution have comparable functional groups, as shown by FTIR spectra. Due to the high yield and purity of isolated Lignin, BL dilution could be a viable alternative in lignin isolation from BL. Moreover, the properties of isolated Lignin are also influenced by BL storage.